Shepherd: the story of a hero dog [videorecording (DVD)] - Roth, Lynn, 1952-; Kravitz, Asher; Maturo, August; Duken, Ken; Zorer, Ayelet (Shout! Factory, 2023)
The timeless, unbreakable bond between a boy and his faithful dog is put to the ultimate test in 1930s Germany. When the Nuremberg Laws are passed forbidding Jews to own pets, Kaleb, a German Shepherd, is separated from his Jewish family and his beloved ten-year-old master Joshua. Kaleb is alone and on the streets, until he is captured and eventually adopted by an SS dog trainer at a Nazi work camp where Kaleb will now be trained to help round up Jews.